(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
The determination of the copolymers of 4-vinylpyridine with styrene copolymers real composition, formed under the conditions of precipitation copolymerization in CCl4, is described. For this, 4-vinylpyridine with styrene was copolymerized in different ratios. The composition of the obtained copolymers was determined according to 1H NMR spectroscopy. A comparison of the real copolymers composition with the theoretically calculated ones was performed as well. The copolymerization of styrene with 4-vinylpyridine was carried out in sealed ampoules in argon medium. Solutions of a concentration of 1.02 mol/l in CCl4 were prepared. The initiator azobisisobutyronitrile in the amount of 0.00106 mol/l was added. The copolymerization was carried out in a thermostat C1823 at T = 75 ± 0.5°C. The copolymerization time was 3 hours. The original ratio of monomers (4-vinylpyridine:styrene) = 6:1; 5:1; 4:1; 3:1; 2:1; 1:2; 1:3; 1:4; 1:5; 1:6. The composition of the obtained copolymers was determined according to 1H NMR spectroscopy. It was determined that copolymers of 4-vinylpyridine with styrene obtained by precipitation copolymerization in CCl4 were enriched by 4-vinylpyridine bonds. On the contrary, the calculation of the instant composition of the copolymers according to the literature shows that under the conditions of classical copolymerization in 4-vinylpyridine solution is less active than styrene. We calculated the theoretical relative constants of copolymerization of styrene with 4-vinylpyridine: r1 = 1.97; r2 = 0.93. Therefore, under the conditions of classical copolymerization in solution 4-vinylpyridine is less active than styrene (r2 < r1). It was also found out that for the original molar content of styrene if it is greater than 0,85, it is not possible to synthesize by means of precipitation polymerization into CCl4 the copolymers of 4-vinylpyridine:styrene.